2009
DOI: 10.1590/s0101-20612009000200019
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação sensorial de bebidas de goiaba adoçadas com diferentes agentes adoçantes

Abstract: A goiaba (Psidium guajava L.), dentre as frutas tradicionais, destaca-se como excelente fonte de vitamina C, além de possuir quantidades razoáveis de pró-vitamina A e vitaminas do complexo B, minerais como cálcio, fósforo e ferro mostra grande aceitação para o consumo in natura (MAIA et al., 2002;CÁCERES, 1999), tornando-se uma fruta muito importante dentro do contexto da fruticultura brasileira. O aumento do consumo está associado à grande divulgação das qualidades nutricionais da fruta (ZANATTA, 2006 CARDEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
2
6
0
7
Order By: Relevance
“…Brito and Bolini (2008a) reported that, in the internal preference map, the guava nectar samples sweetened with sucrose, sucralose, aspartame, and cyclamate/saccharin (2:1) were closer to each other and had a high concentration of consumers, while the sample sweetened with stevia was the least accepted. Fernandes et al (2009) found, in the internal preference map, a great proximity between the guava nectar samples sweetened with aspartame and sucrose, which were the most accepted. …”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Brito and Bolini (2008a) reported that, in the internal preference map, the guava nectar samples sweetened with sucrose, sucralose, aspartame, and cyclamate/saccharin (2:1) were closer to each other and had a high concentration of consumers, while the sample sweetened with stevia was the least accepted. Fernandes et al (2009) found, in the internal preference map, a great proximity between the guava nectar samples sweetened with aspartame and sucrose, which were the most accepted. …”
Section: Resultsmentioning
confidence: 88%
“…Fernandes et al (2009) observed that samples of guava nectar sweetened with sucrose and aspartame were more accepted in terms of flavor, while the sample to which stevia was added had lower acceptance for this attribute. The purchase intent results showed that the samples of acerola nectar sweetened with sucrose and sucralose had the highest frequencies of positive purchase intent, corresponding to the responses "I would certainly buy" and "I would probably buy", totaling 67.49% and 63.33%, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Pesquisas indicam que os brasileiros têm uma maior preferência por produtos doces, com alto teor de açúcar (SOLOMON & RIBEIRO, 2011). Em estudo realizado com cem julgadores não treinados, houve 81% de aceitação para a doçura de bebidas de goiaba, adoçadas com 11% de sacarose (FERNANDES et al, 2009). Além disso, a faixa etária jovem (julgadores predominantes do atual estudo) e, em especial, a cultura mineira apresentam tal hábito alimentar (FISBERG, et al, 2000;ABDALA, 2006;MOMO et al, 2006;ESTIMA et al, 2009).…”
Section: Methodsunclassified
“…Diversos estudos têm sido realizados utilizando essa técnica para avaliar a aceitação de produtos pelo mercado consumidor (Miquelim et al, 2008;Sales et al, 2008;Fernandes et al, 2009;Reis et al, 2009).…”
Section: Introductionunclassified